Maternal Effects of Exercise Training on the Critical Thermal tolerance, Critical Swimming speed, and response to a Heatwave simulation in the juvenile brown trout (Salmo trutta) - Saarinen, Ulla (My University, 2022)
Heatwaves cause a notable threat to the ectothermic animals whose body temperature depends entirely on the ambient temperature. Prolonged high temperatures negatively affect fish physiology, as they may cause internal oxygen deficiency and therefore complications in the swimming performance. A particular concern should be directed towards farmed fish, as they suffer from a compromised physiological performance in comparison to their wild conspecifics. Therefore, their ability to tolerate heatwaves is also compromised. Moreover, the stocked offspring of farmed fish are reported to have extremely low changes to survive till maturity. The aim of this study was to explore whether the offspring of swim trained hatchery brown trout (Salmo trutta) have inherited beneficial traits that could improve their thermal tolerance and swimming capacity to adjust to heatwaves. For this purpose, we exposed frystaged and parr-staged juvenile offspring of trained and non-trained dams to a 3-week heatwave simulation and measured their critical thermal maximum (CTMAX) and critical swimming speed (UCRIT). The results showed that the training background do not significantly alter the CTMAX and UCRIT performance. However, the heatwave exposure revealed a trend where the trout with a training background were more phenotypically plastic regarding CTMAX and UCRIT. These findings suggest that training the dams before the reproduction period does not have negative consequences to the offspring. However, training background has an inducing effect on the phenotypic plasticity of juvenile-staged trout, yet more studies are required. All in all, this study gives unique knowledge about the maternal effects of swimming training and provides a path for the future projects.
Keywords: Heatwave, swimming exercise, transgenerational effects, brown trout, aquaculture